HYGIENE SANITASI PEMBUATAN SOHUN PT. SOKA INDAH DESA KARANGSOKA KECAMATAN KEMBARAN KABUPATEN BANYUMAS TAHUN 2018 - Izza Anzili Rizqi; Zaeni Budiono (Poltekkes Kemenkes Semarang, 2019)
Sohun is a dry food product made from starch with a distinctive shape. Utilization of vermicelli is still limited as a mixture of foods such as soup, soup, meatballs, kimlo and salad. Sohun is often used in vegetarian food or is added in drinks, sweets or dessert soups. Along with the use of vermicelli, consuming noodles should pay attention to the quality of the noodles. Improper quality of noodles can interfere with health, decreased health status due to poor sanitary hygiene conditions. The purpose of this research is to know the score of assessment of applying sanitation hygiene making of vermicelli at PT. Soka Indah Karangsoka Village Kembaran Sub-district Banyumas Regency In 2018. The results showed the scores of sanitation hygiene scores on the selection of foodstuffs were eligible because of the 100% score. Storage of foodstuffs, food processing, food transport, food packaging, food storage and sanitation facilities are not eligible for a score of 76%. Sanitary condition of making vermicelli as a whole did not meet the requirement because obtained score 58.4%. Hygiene sanitation making vermicelli PT. Soka Indah Karangsoka Village Kembaran Sub-district Banyumas Regency is not eligible, sanitation hygiene problem can be overcome with special attention to improve the hygienic principles of sanitation of vermicelli management from the selection process of foodstuff, food storage, food processing, food transportation, food packaging and food storage, sanitation facilities and conditions of temperature, humidity and lighting in each workspace of PT. Soka Indah